An investigative study on replacing the conventional furnaces of naphtha reforming with chemical looping combustion for clean hydrogen production. (31st July 2020) - Ebrahimian, Samira; Iranshahi, Davood
Abstract: This paper presents a new design for the thermal coupling of the naphtha reforming process with chemical looping combustion (CLC-NR). In this integrated configuration, the chemical looping combustion (CLC) process provides the required heat of the endothermic naphtha reforming process. Hence, intermediate heaters of conventional naphtha reforming (CNR) used to adjust the feed temperature of the reactors were eliminated. Another modification was the replacement of the first conventional furnace of CNR with a novel CLC assisted furnace (CLC-Furnace) to increase the naphtha feed temperature to 777 K. CLC and naphtha reforming processes were considered to occur in fixed-bed reactors in which feed streams can be introduced radially either in inward or outward flow patterns. Results showed that the molar flow rates of aromatics produced in an inward flow pattern are 2 k m o l / h higher than the outward flow. In order to increase the surface area where the heat transfer takes place, the thermally coupled reactors were divided into some subsections which increased the aromatics and hydrogen production rates by 145 k m o l / h and 1502 k m o l / h, respectively. The performance of the novel configuration and conventional radial-flow naphtha reforming (RF-CNR) reactor was also compared demonstrating 10% increase in aromatics production. Graphical abstract: Image 1 Highlights: Thermally coupling of naphtha reforming with chemical looping combustion. Enhancement in hydrogen and aromatic production. Using the heat of the air reactor instead of fossil fuel furnaces. Carbon dioxide capture in the naphtha reforming plant. Comparing the inward and outward flow patterns in thermally coupled reactors.